Investigating the Components of Transformational Leadership: A Qualitative Study on the National Iranian Oil Terminals Company (NIOTC) - Biramvand, Samira; Manzari Tavakoli, Hamdollah; Kamali, Mohammad Jalal; Shokouh, Zahra; Fatehi Rad, Navid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This study aims to investigate the components of transformational leadership within the National Iranian Oil Terminals Company (NIOTC), providing insights into how this leadership style can be effectively implemented to enhance organizational outcomes in the oil and gas sector. Methodology: This qualitative research employed semi-structured interviews with 19 experienced managers and academic experts from NIOTC. The participants were selected using a theoretical sampling approach until theoretical saturation was achieved. Data was collected through detailed interviews and analyzed using NVivo software to identify key themes and patterns related to transformational leadership. Findings: The analysis revealed several critical components of transformational leadership at NIOTC, including creating a dynamic organizational vision, setting elevated goals, supporting organizational learning, transforming cultural values, fostering organizational trust, linking individual and collective interests, providing inspirational motivation, stimulating intellectual engagement, enhancing followers’ adaptability, and considering individual needs. These components align with existing literature on transformational leadership and highlight the importance of vision, motivation, trust, and adaptability in driving organizational success. Conclusion: The findings of this study provide a comprehensive understanding of transformational leadership within NIOTC. Effective transformational leaders at NIOTC emphasize creating a compelling vision, fostering a culture of continuous learning, innovation, and trust, and aligning individual and organizational goals. These insights can guide leaders in similar contexts to implement transformational leadership practices that enhance organizational performance and employee development. Future research should explore these components in different organizational and cultural settings to further validate and expand on these findings.